Order the the steps to solve the equation for x. Make sure to put the steps in order. Not all steps will be used.

-6(x + 3) +x = -6x + 30
Step 1
Step 2
Step 3
Step 4
Final Answer
x = 12
-6x -18 + 4x = -6 x + 30
-6x +3 + 4x = -6x + 30
4x - 18 = 30
-8x + 3 = 30
-2x -18 = -6x + 30
4x = 48
-8x = 27
x = -27/8
x = 12
-6x -18 + 4x = -6 x + 30
-6x +3 + 4x = -6x + 30
4x - 18 = 30
-8x + 3 = 30
-2x -18 = -6x + 30
4x = 48
-8x = 27
x = -27/8

1 answer

Step 1: Distribute the -6 and simplify the expression: -6(x + 3) + x = -6x - 18 + x = -7x - 18
Step 2: Combine like terms: -7x - 18 + 4x = -7x + 4x - 18 = -3x - 18
Step 3: Combine like terms: -3x - 18 = -6x + 30
Step 4: Add 6x to both sides and subtract 30 from both sides: -3x - 18 + 6x - 30 = -6x + 30 + 6x - 30
Final Answer: 3x - 48 = 0
x = 16